Artificial incubation does not affect the post-hatch development, health, or survival of the Lance-tailed Manakin (Chiroxiphia lanceolata), a tropical passerine. (19th March 2019) - Jones, Blake Carlton; DuVal, Emily H
Abstract: Artificial incubation of avian eggs is used in scientific research, conservation, zoo husbandry, and the commercial poultry industry. However, whether artificial incubation negatively impacts post-hatch nestling phenotypes and survival compared to naturally incubated young has not been explicitly tested. Here, we assess whether nestlings artificially incubated as eggs and returned to their natal nest after hatching experienced negative impacts in development, health, and survival. From 2007 to 2017, we measured mass, mass growth rate, tarsus length, tarsus growth rate, external lesions, ejection from the nest, fledging success, and recruitment of Lance-tailed Manakin ( Chiroxiphia lanceolata ) nestlings from 209 nests where 1 of 2 eggs was artificially incubated, along with 230 unmanipulated nests. We found no statistically significant difference in the development, health, and survival among nestlings artificially incubated as eggs, their naturally incubated nestmates, and nestlings from unmanipulated nests. Our results indicate that artificial incubation can be a safe and effective tool in the study of free-living birds.